Pre-clinical pharmacology of ICI D2138, a potent orally-active non-redox inhibitor of 5-lipoxygenase. - McMillan, R. M. (1992)
1. This paper describes the pre-clinical pharmacology of ICI D2138, a potent orally-active non-redox inhibitor of 5-lipoxygenase which is undergoing clinical evaluation. 2. ICI D2138 potently inhibited leukotriene synthesis in murine peritoneal macrophages (IC50 = 3 nM) and human blood (IC50 = 20 nM). In human and dog blood, ICI D2138 did not inhibit thromboxane B2 synthesis at a concentration of 500 microM, thus the selectivity ratio (cyclo-oxygenase: 5-lipoxygenase) was greater than 20,000. In contrast, zileuton (a 5-lipoxygenase inhibitor also undergoing clinical evaluation) exhibited a selectivity ratio of 15-100. 3. ICI D2138 potently and dose-dependently inhibited ex vivo leukotriene B4 (LTB4) synthesis by rat blood with ED50 values of 0.9, 4.0 and 80.0 mg kg-1 p.o. at 3, 10 and 20 h respectively after dosing. Similar activity was observed for inhibition of LTB4 production in a zymosan-inflamed rat air pouch model. Zileuton produced ED50 values of 5 and 20 mg kg-1 at 3 and 10 h respectively. 4. Oral administration of 1, 3 or 10 mg kg-1 ICI D2138 to dogs produced maximal inhibition of ex vivo LTB4 synthesis by blood for 5, 9 and 31 h respectively. A dose of 5 mg kg-1 p.o. of zileuton caused maximal inhibition of LTB4 for 24 h. 5. Oral administration of 10 mg kg-1 ICI D2138 caused total inhibition of LTB4 production in zymosan-inflamed rabbit knee joint. 6. Topical administration of ICI D2138 to rabbit skin caused a dose-related inhibition of arachidonic acid-induced plasma extravasation with an ID30 of 1.08 nmol per site.(ABSTRACT TRUNCATED AT 250 WORDS)